Anthropological profile of U16 basketball players - Borovic, I.; Rupcic, T.; Matkovic, B. R.; Garafolic, H.; Dadic, M. (Acta Kinesiologica, 2016)
The purpose of this study was to analyse the anthropological profile of top level U16 basketball players, members of the Croatia U16 men`s national team, with the aim of defining model values that shall in the future serve the purpose of directing and developing basketball players in the chosen age group. Eleven (11) potential members of the U16 men`s national basketball team participated in this research, with an average age of 15.72±0.44 years. The variable sample was composed of morphological characteristics and tests for evaluating motor and functional skills. Data processing was implemented by applying the statistical software package Statistica for Windows, ver. 12. Basic descriptive statistical parameters were calculated and demonstrated for each variable. On the basis of the obtained results for the measured morphological characteristics, the conclusion can be made that, already in the U16 age category, a difference can be noticed between the longitudinal and transverse dimensionality of the skeleton between the guard - forward - centre player positions, although a complete specialisation for each single player position is very often not final at that age. Likewise, results obtained for the percentage of body fat indicate that all players in this sample group of examinees have an optimal body composition. In almost all motor skill tests, the best results are achieved by guards, whereas the biggest differences between players in different positions are noticeable in tests for examining speed, agility and explosive strength. Aerobic and anaerobic capacities are well developed in all players and they meet the high demands of playing modern basketball.